The UK Citizens Advice service and the plurality of actors and practices that shape "legal consciousness". Issue 3 (1st September 2016) - Kirwan, Samuel
ABSTRACT: The UK presents an extreme case of the "austerity" politics that define "access to justice" across several "global north" contexts. This paper addresses a dimension of law within this distinct "global north" setting that has been brought into relief by these changes, namely the key role played by advice services in "translating" legal frameworks for individuals seeking to understand and engage with the legal problems that are dominating their lives. They bring into relief, that is, the plurality of actors involved in shaping the ways in which legal frameworks are discussed and interpreted, a plurality that disrupts the dominant image in which a group of experts provide information for a homogenous public. Noting the importance for understanding "legal consciousness" of engaging with these plural actors and practices, drawing upon research carried out with the UK Citizens Advice service the paper investigates the different ways in which legal information is translated across the varying emotional dynamics of the adviser–client relationship. It describes how advice work incorporates a "relational legal labour", a work seeking to transform the client by enabling a "shifting of attachments".